The performance of public health sector in Aceh, Indonesia - Nanda Nur Sofyana (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
Abstract This study analyses performance measurement of public health sector in Aceh province, where this province consists of 17 municipalities and 5 cities. The measurement issue in this study is in terms of efficiency by using a non-parametric method that is Data Envelopment Analysis (DEA). There are two findings that can be applied in policy implications. First, this paper explains the performance measurement of public sector in Aceh using output and input variables. Second, another key finding in this study is to obtain information regarding which district called efficient and vice versa.